State institutes and the Czechoslovak Academy of Sciences, 1948–1953 - Adéla Jůnová Macková (Studia Historiae Scientiarum)
State institutes started emerging shortly after the establishment of the first Czechoslovak Republic (1918) in the form of institutions affiliated to the Ministry of Schools and National Education. They were independent scientific institutions receiving regular state subsidies and their scientific focus and budgets were approved by the state.